In Vivo Morphological Study of Common Canalicular Orifice and Its Impact on Lacrimal Probing. Issue 4 (July 2020) - Singh, Swati; Curragh, David S.; Davis, Gary; Selva, Dinesh
Abstract : Purpose: To study the in vivo morphology of common canalicular/lacrimal sac mucosal folds (CLS-MFs) and their relationship with probing findings. Methods: Consecutive cases undergoing endoscopic dacryocystorhinostomy had endoscopic examination of the internal canalicular orifice (ICO). Details of CLS-MFs folds, probing findings, and outcomes of dacryocystorhinostomy were analyzed. Results: Thirty-six lacrimal systems of 34 patients (mean age, 58 years; 7 males, 27 females) were examined. All 36 lacrimal systems had a single common canalicular orifice entering the lacrimal sac (100%). Overall, 61.1% (22/36) had visible CLS-MFs, out of which only 13.6% (3/22) were overhanging the ICO requiring manipulation of the probe to enter the lacrimal sac. The orientation of folds was superior 180° in 2, posterosuperior in 2, posterior in 6, inferior 180° in 6, and inferior 270° (excluding 10–2′o clock quadrant) in 6 systems. Two cases preoperatively labeled as having common canalicular obstruction, based on lacrimal syringing, had CLS-MFs impacting against the ICO without any anatomical obstruction. One of 5 cases with lacrimal sac mucocele had CLS-MFs located along the posterosuperior edge extending for 270°, which resulted in a soft stop on preoperative lacrimal syringing findings. Only 1 case had a true membrane (2.7%) overlying the ICO, which required excision. No differences in outcomes of dacryocystorhinostomy were observed between cases with CLS-MFs versus without any folds. Conclusion: CLS-MFs display a wide variation in terms of morphological location and extent along the ICO. They might be responsible for the false soft stop observed in some cases on preoperative syringing and do not require excision. Abstract : Common canalicular/lacrimal sac mucosal folds usually do not interfere with internal canalicular opening and overlay the orifice in 13.6% patients.